2022
DOI: 10.1002/ctm2.1038
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proteasomal deubiquitinases USP14 and UCHL5 overcomes tyrosine kinase inhibitor resistance in chronic myeloid leukaemia

Abstract: Background Chronic myeloid leukaemia (CML) is a haematological cancer featured by the presence of BCR‐ABL fusion protein with abnormal tyrosine kinase activation. Classical tyrosine kinase inhibitor (TKI)‐based therapies are available to patients with CML. However, acquired resistance to TKI has been a challenging obstacle, especially stubborn T315I mutation is the most common cause. Therefore, it is especially urgent to find more effective targets to overcome TKI resistance induced by BCR‐ABLT315I. Proteasoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Inhibition of USP14 has been demonstrated to induce autophagy (Han et al., 2019; Wu et al., 2022; Xu et al., 2016), apoptosis (Liao et al., 2018; Wu et al., 2022), and ferroptosis (Tsai et al., 2020), by which reversing drug resistance in breast cancer, melanoma, and chronic myeloid leukemia, etc. (Jiang et al., 2022; Selvaraju et al., 2015; Shen et al., 2020; Wu et al., 2022; Xia et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of USP14 has been demonstrated to induce autophagy (Han et al., 2019; Wu et al., 2022; Xu et al., 2016), apoptosis (Liao et al., 2018; Wu et al., 2022), and ferroptosis (Tsai et al., 2020), by which reversing drug resistance in breast cancer, melanoma, and chronic myeloid leukemia, etc. (Jiang et al., 2022; Selvaraju et al., 2015; Shen et al., 2020; Wu et al., 2022; Xia et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…B-AP15, an inhibitor of USP14 and UCHL5, can cooperate with imatinib to inhibit the growth of BCR-ABL-WT and BCR-ABL-T315I CML cell lines, CML xenograft tumor, and primary CML cells. 154 Meanwhile, in another study, they found that piperlongumine, isolated from piper longum L., can target USP14 and UCHL5 to inhibit the proteasome function of CML cells with or without T315I mutation, weaken the cell viability of CML cell line, induce apoptosis, and inhibit the growth of transplanted tumor. This study provides a theoretical basis for the application of piperlongumine in patients with CML resistance.…”
Section: The Ups In CML Tki-resistancementioning
confidence: 99%
“…b-AP15 has demonstrated the ability to induce strong oxidative stress and cell death in various cancer cells and inhibit tumor growth in mice. [78][79][80] Preclinical studies have also shown that USP14 and UCHL5 inhibitors exhibit broad antitumor activity against both nonsolid and solid tumors (e.g., multiple myeloma and hypopharyngeal carcinoma), overcoming resistance to bortezomib. 78,81 This indicates that their mechanism of action against cancer is distinct from that of 20S proteasome inhibitors.…”
Section: Dual Inhibitors Of Usp14 and Uchl5mentioning
confidence: 99%
“…b‐AP15 possesses an α, β‐unsaturated carbonyl moiety, which is highly prone to undergoing a Michael addition reaction with nucleophilic cysteine thiolates of DUBs. b‐AP15 has demonstrated the ability to induce strong oxidative stress and cell death in various cancer cells and inhibit tumor growth in mice 78–80 . Preclinical studies have also shown that USP14 and UCHL5 inhibitors exhibit broad antitumor activity against both nonsolid and solid tumors (e.g., multiple myeloma and hypopharyngeal carcinoma), overcoming resistance to bortezomib 78,81 .…”
Section: Therapeutic Potential Of Dub Inhibitorsmentioning
confidence: 99%